CONSUMER LOYALTY REVIEWED FROM BRAND IMAGE, SOCIAL MEDIA, LIFESTYLE AND PRODUCT INNOVATION (Study on iPhone Users in Solo ) - Enggar Arifina; Sudarwati Sudarwati; Bambang Mursito; Dewi Hermawati Wahyuningsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The research was conducted with the aim of knowing and explaining the influence of Brand Image, Social Media, Lifestyle, and Product Innovation on Consumer Loyalty of iPhone Users in Solo City. The distribution of questionnaires and documentation of iPhone users in the city of Solo who agreed to be respondents was chosen to be the data collection technique in this study. The sample for this study was 125 respondents with convenience sampling. The results of this study are that the variables of Brand Image, Social Media, Lifestyle and Product Innovation together or simultaneously have a significant effect on Consumer Loyalty of iPhone Users in the City of Solo. Partially, each variable, namely Brand Image, Social Media, Lifestyle and Product Innovation, has a significant effect on Consumer Loyalty of iPhone Users in the City of Solo. Overall Variables of Consumer Loyalty Overall the variables of Brand Image, Social Media, Lifestyle and Product Innovation which are explained by the independent variables are 52.20% and the rest are obtained from other variables. Keywords: Social Media, Lifestyle and Product Innovation, Consumer Loyalty